Oral Health Problems Perceived: Electronic Cigarettes versus Conventional Smokers - Indri Lubis; Sayuti Hasibuan; Aisyah Noer; Hertika Sari Sinabutar (TALENTA, 2024)
Electronic cigarettes are currently becoming a new trend for smokers, particularly among youth and young adults. Oral health problems related to their use are still not fully understood compared to the adverse effects of conventional cigarettes that are widely recognized. Therefore, this study aimed to compare oral health problems perceived between electronic cigarette users and conventional smokers. The method used was an observational cross-sectional design comprising 100 enrolled college students at Universitas Sumatera Utara. Electronic cigarette users and conventional smokers were invited to participate in the study and data collection was carried out using a questionnaire. Frequencies and percentages were obtained for socio-demographic, Cigarette Dependence Index, and self-perceived oral health problems due to smoking according to their status. A Chi-square test was used to assess the variation between the study groups with the different factors. The result showed that there was no statistical difference in oral health problems perceived between electronic cigarettes and conventional smokers (p = 0.648). Irritation of the mouth, cracked or broken tooth, and dry mouth were more prevalent in electronic cigarettes at 24%, 36%, and 64%, compared to conventional smokers at 14%, 28%, and 56%, respectively. In conclusion, this study observed no difference in oral health problems perceived between electronic cigarette users and conventional smokers.